Acceleration-Based Vibration Control for Structural Systems with Actuator Faults and Finite-Time State Constraint. (April 2015) - Weng, Falu; Ding, Yuanchun; Liang, Liming; Ge, Ji
The problem of acceleration-based vibration control for structural systems with actuator faults and finite-time state-constraint is discussed in this paper. The objective of designing controllers is to guarantee the closed-loop systems satisfying a finite-time state-constraint condition while having a prescribed level of acceleration attenuation performance. First, by describing the actuator faults into a fault matrix, the actuator-fault-included state-space model, with the acceleration as its controlled output, is obtained. Then, based on a combination of matrices and rank-1 vectors, the obtained model is extended to its uncertain description which contains parameter uncertainties appearing in all the mass, damping and stiffness matrices. Second, based on the finite-time stability analysis, the sufficient conditions for the existence of acceleration-based vibration controllers are obtained. By solving these conditions, the desired controllers, with considerations of actuator faults and parameters uncertainties, are obtained for the closed-loop system to be stable with finite-time state-constraint and acceleration-based H-infinite performance. In the end, simulation results are given to show the effectiveness of the proposed theorems.